The Effort of Parent-Child Reading Activity in Chinese Traditional Family Education: A Practical Study in a Primary School of Shenzhen - Kang Yaqiong; Wang Lijie; Kang Yanan (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2022)
China is a country with traditional family education. Parents greatly influence their children, especially under the one-child policy and urbanization background. Chinese teaching requires context and training. Reading and communication are important ways to improve Chinese. Parent-child reading can better help students in grades 1-3 to read. This article aims to compare students' performance and interview results of parents in an elementary school in the immigrant city, Shenzhen, Guangdong Province, China, to explore the supporting role of parents in this family education. Previously, similar language research work has examined the students' language development in Shenzhen Pontus' families for further research. This study used mixed methods to analyze the parent-child reading situation in a school in Shenzhen. This article also compared the students' Chinese performance to judge the impact of parent-child reading on students. The results show that the influence of parent-child reading in family education has an obvious positive effect. The specific auxiliary role is reflected in children's reading ability, Mandarin level, and literary knowledge. Therefore, this study suggests that teachers and parents promote parent-child reading work. Parent-child reading is not only conducive to the psychological growth of students but also conducive to the cultivation of students' language ability, especially for the cultivation of students' Mandarin and literary ability.